Engineered Male Sterility by Early Anther Ablation Using the Pea Anther-Specific Promoter PsEND1 - Roque, Edelín; Gómez-Mena, Concepción; Hamza, Rim; Beltrán, José Pío; Cañas, Luis A. (Frontiers in Plant Science, 2019)
Genetic engineered male sterility has many applications, such as hybrid seed production or bioconfinement of transgenes in genetic modified crops. The impact of this technology is currently patent in a wide range of crops, including legumes, and this has helped in encountering the challenges of global food security. Production of engineered male sterile plants by expression of a ribonuclease gene under the control of an anther- or pollen-specific promoter has proven to be an efficient way to generate pollen-free elite cultivars. In the last years, we have been studying the genetic control of flower development in legumes and several genes that are specifically expressed in a particular floral organ were identified. Pisum sativum ENDOTHECIUM 1 (PsEND1) is a pea anther-specific gene that displays early expression in the anther primordium cells. This expression pattern has been assessed in both model plants and crops (tomato, tobacco, oilseed rape, rice, wheat) using genetic constructs carrying the PsEND1 promoter fused to the uidA reporter gene. This promoter fused to the barnase gene produces full anther ablation at early developmental stages, preventing the production of mature pollen grains in all plant species tested. Additional effects produced by the early anther ablation in the PsEND1::barnase plants, with interesting biotechnological applications, have also been described, such as redirection of resources to increase vegetative growth, elimination of pollen allergens or reduction of the need for deadheading to extend the flowering period in ornamental plants (Kalanchoe, Pelargonium). Moreover, early anther ablation in PsEND1::barnase tomato plants triggers the developing of the transgenic ovaries into parthenocarpic fruits, in the absence of the signals usually generated during pollination and fertilization. Early anther ablation in tomato can be considered an efficient tool to promote fruit set and to obtain seedless and good quality fruits. PsEND1::barnase plants are also useful to generate parental lines to be used in hybrid breeding approaches to produce new cultivars in different legume species.